"Mas professora, isso é arte?": uma abordagem antropológica da arte na sala de aula - Tragante, Christiane Aparecida (2011)
This dissertation is an anthropological study about the relations constructed by children of art and its objects in Art-Education classes. Following concerns built from my experience as a teacher, I have conducted an ethnographical research that pointed out to differences in the definition, classification and contemplation of art objects between students and teachers at Art-Education classes. From an ethnography carried out at two 5th grades of elementary education at public schools in Sao Carlos-SP, it was possible to notice on processes of construction of knowledge that children, besides teachers, as well as art objects and other field agents, are active subjects in those learning relationship. Their drawings contributed to highlight that relationships constructed in the teaching-learning process affect the ways of knowing, appreciating and making art. They also showed that children act in a particular way toward art objects. Finally, ethnography led to reflections about art-education for children, as well as about our own art system.